Investigations on the morphology and conductivity of peo / enr-25 / liclo4 blend in relation to atr-ftir study on the blends / Nurhayati Kamyon - Kamyon, Nurhayati (2010)
Blends of PEO/ENR/LiC104 were prepared by solution casting technique. Conductivity (er) of poly(ethylene oxide) (PEO), a semicrystalline polymer and an amorphous epoxidized natural rubber with 25 mol% epoxidation level (ENR-25) doped with Y = 0.00 to Y = 0.20 (lithium perchlorate) LiC104 were studied by Impedance spectroscopy. The conductivity results show that the Li salt dissociates more in PEO than in ENR-25.The morphology of the blends were studied using polarized optical microscope (POM). Incorporation of LiC104 to neat PEO and the PEO/ENR blends suppress the crystallinity of PEO leading to the observation of widening area of amorphous region in the once volume filled morphology of PEO. The Fourier transform infrared (FTIR) studies were carried out using Nicolet FTIR and data from the FTIR spectra show a reduction in the crystallinity of PEO as observed in the changes in the characteristic peaks assigned to the crystalline region of PEO. No dipole-dipole interaction between PEO and ENR-25 were observed from the FTIR spectra of the various composition of the blend.